the Efektivitas Model Pembelajaran Stratagem dibandingkan Think Pair Share dalam Edukasi Pencegahan Seks Pranikah Remaja - Muhammad Bachtiar Safrudin (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2026)
Adolescent growth and development cause physical, cognitive and psychosocial changes followed by sexual maturity followed by attraction to the opposite sex, thus triggering the potential for premarital sexual behavior. This problem requires preventive measures in the form of health education. Current education methods are only classical without considering the needs and interests of students. So the think pair share (TPS) and stratagem models are solutions to increase students' interest in following health education. The purpose of this study was to see the difference in the effectiveness of the think pair share and stratagem health education methods on knowledge of premarital sex prevention. The design of this study used Quasy Experimental pre and post with control group design. The population in this study were 120 class X students of SMA 11 Samarinda. The sampling technique used random sampling with 42 people for each sample. Knowledge of adolescent student prevention was measured by a questionnaire consisting of 16 question items. The results of the study showed a change in knowledge score of 4 given in the TPR learning model while in the Stratagem model there was an increase of 6. The results of the Mann Whitney test showed a p value of 0.000 <0.05 which means there is a difference between the TPS and Stratagem models. The Stratagem model is suitable for teenagers because the character of teenagers who like relaxed and fun learning.